SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN PENERIMA PROGRAM KELUARGA HARAPAN (PKH) DI NAGARI AIA BATUMBUAK MENGGUNAKAN METODE ANALITHICAL HIERARCHY PROCESS (AHP) - Veni Wedyawati; Eko Amri Jaya; Marya Nelsa Achsani (Sekolah Tinggi Teknologi Industri Padang, 2021)
Decision support systems (SPK) are generally defined as a system capable of producing problem solving. Decision support systems are not intended to replace the role of decision makers, but to help and support decision makers. One method that is often used in decision-making systems is the method of analytic hierarchy process (AHP). This AHP method was chosen because this method can describe complex multi-factor problems or multi criteria into a hierarchy. with a hierarchy a problem will appear more structured and systematic. The family hope program (PKH) is one of the assistance provided by the government to the underprivileged people who are eligible to receive cash assistance. With the analithal hierarchy process (AHP) method, it is expected that the assessment will get maximum results. This decision support system is designed using visual basic.net programming language.